Manuel Amunategui. First fifty years of El Comercio - Leonardini Herane, Nanda (2023)
In 1839, the Chilean Manuel Amunátegui, together with the Argentinean Alejandro Villota, founded in the city of Lima the newspaper El Comercio, known today as Dean of the National Press. This article, whose main objective is to rescue the figure and journalistic work of this important man for the history of Peruvian journalism, relates the life and intellectual work of Amunátegui intimately linked to the first fifty years (1839-1889) of El Comercio, a newspaper with a clear liberal stance since, from its beginnings, it advocated the abolition of slavery, the suppression of indigenous tribute and freedom of the press. However, due to health problems, Amunátegui was forced to sign a partnership agreement in 1876 with José Antonio Miró Quesada and Luis Carranza Ayarza, which led to a change in the newspaper’s line towards a commercial and essentially political one. The new phase of El Comercio coincided with the effects of the War of the Pacific in the country, and the deterioration of his health. After his death, he was recognised in some newspapers of the time as one of the greatest exponents of Peruvian journalism. His contribution to the training of the new generation of journalists is also highlighted until today.